Which skills are the most prized? Analysing monetary value of geographers’ skills on the labour market in six European countries - Piróg, Danuta; Hibszer, Adam (Quaestiones Geographicae, 2023)
The objective of the study is to identify those skills that are actually needed by the labour market and allow university graduates to achieve the highest remuneration. To achieve this objective, the authors monitored, for 18 months, online job postings from six countries addressed to geography graduates. Online job postings are the most up-to-date and reliable source of data about the salaries that employers are willing to offer for specific skills or skillsets. A total of 17,397 advertisements were collected, out of which 7,407 included information about the offered salary. Applying text mining and regression tree (classification and regression tree [CART]) analyses, the authors identified skills that significantly differentiate annual salaries. The group of competences associated with higher earnings includes highly specialised geographic information system (GIS), statistical and geological skills. Lower salaries were linked to some general skills such as communicating in a native language as well as some specialised skills, but only to those related to teaching and conducting scientific research.